UCTS Foundation students’ perception towards Arduino as a teaching and learning tool in STEM education - Ong, Sing Ling; Ling, Jill Pei Wah (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper presents the perception of University College of Technology Sarawak (UCTS) students on the implementation of the Arduino lessons incorporated in Foundation in Science (FIS) and Foundation in Arts (FIA) programmes as part of STEM education. The low number of students studying or applying for STEM fields has been alarming in regards to the nation’s future workforce needs. Efforts have been made to attract more students to STEM programmes and careers. This study is intended to examine whether Arduino, as a teaching and learning tool, helps in generating students’ interests towards STEM programmes. Arduino is one of the physical computing tools which has open-source electronics platform based on user-friendly hardware and software for creating different projects and applications. Arduino is easy to be used by beginners, yet flexible enough for advanced users to learn physical computing and programming. Results revealed that participating students felt that they learnt programming the most during Arduino learning process and Arduino is proven to cultivate their STEM interests and 21st century skills. In this paper, the students' awareness and experiences on learning Arduino in STEM education were studied. This study can be used to determine whether educational institutions should implement Arduino lessons to promote STEM interests among the students which further lead them to opt for STEM-related degree programmes and careers.